mTOR Inhibitor Use Is Associated With a Favorable Outcome of COVID-19 in Patients of Kidney Transplant: Results of a Retrospective Study - Pinchera, Biagio; Spirito, Lorenzo; Buonomo, Antonio Riccardo; Foggia, Maria; Carrano, Rosa; Salemi, Fabrizio; Schettino, Elisa; Papa, Fortuna; La Rocca, Roberto; Crocetto, Felice; Napolitano, Luigi; Villari, Riccardo; et al. (Frontiers in Medicine, 2022)
Introduction In solid organ transplant recipients, COVID-19 is associated with a poor prognosis because of immunosuppression. Some studies suggest a potential therapeutic role of mammalian Target of Rapamycin (mTOR) inhibitors in SARS-CoV-2 infection. This study aimed to assess the impact of mTOR employment on the evolution and outcome of SARS-CoV-2 infection in solid organ transplant recipients. Methods We enrolled kidney transplant patients attending the Azienda Ospedaliera Universitaria Federico II in Naples and followed up on these patients from March 2020 to June 2021. We evaluated the risk of acquiring the SARS-CoV-2 infection, the clinical presentation of the disease, and its outcome together with the type of immunosuppressive therapy. Finally, we assessed the impact of mTOR inhibitors on relevant clinical metrics of SARS-CoV-2 infection. Results We enrolled 371 patients, of whom 56 (15.1%) contracted SARS-CoV-2 infection during the period of the study. There were no differences observed among the different immunosuppressive therapies concerning the risk of acquiring SARS-CoV-2 infection. In contrast, the type of immunosuppressive therapy had a significant impact on the outcome of the disease. In detail, patients who received mTOR inhibitors, as part of their immunosuppressive therapy, compared to other regimens had a lower chance of developing a moderate or severe form of the disease (OR = 0.8, 95, CI: (0.21–0.92), P = 0.041). Conclusion In kidney transplant patients, the use of mTOR inhibitors as part of an immunosuppressive regimen is associated with a better prognosis in the case of COVID-19.